A Comprehensive Literature Review of Long-Term Use of Muscle Relaxant Medications for Chronic Pain - Stefanus, Stefanus; Aditya, Aditya; Andhika, Andhika (The International Journal of Medical Science and Health Research, 2024)
Background: The literature on the long-term use of muscle relaxant medications for chronic pain reveals a nuanced landscape characterized by varying degrees of efficacy, safety concerns, and the potential for combination therapies. The introduction establishes the complexity of chronic pain management, emphasizing the need for a multifaceted approach that includes both pharmacological and non-pharmacological interventions. Literature Review: The systematic reviews by (Orrillo et al., 2022) and (M. Weisman et al., 2024) provide a critical lens on the efficacy and tolerability of muscle relaxants, revealing a lack of substantial evidence supporting their long-term use in chronic pain management. The findings emphasize the need for cautious application of these medications, particularly given the potential for adverse effects and the ambiguities surrounding their effectiveness over extended periods. Lastly, the exploration of muscle relaxants' role in post-chemotherapy and radiotherapy contexts, as discussed by (Radkowski et al., 2024), broadens the scope of their application, indicating that muscle relaxants may serve a critical function beyond traditional pain management. This perspective encourages further inquiry into their long-term efficacy and safety in various clinical settings. Conclusion: In conclusion, the literature presents a complex picture of muscle relaxants in chronic pain management. While they may provide short-term relief, their long-term use raises significant safety and efficacy concerns. The integration of combination therapies and non-pharmacological interventions appears crucial for optimizing treatment strategies. Future research is necessary to clarify the long-term implications of muscle relaxant use and to establish more definitive guidelines for their application in chronic pain management.